Cardiac‐specific overexpression of caveolin‐3 preserves t‐tubular ICa during heart failure in mice. Issue 5 (14th March 2019) - Kong, Cherrie H. T.; Bryant, Simon M.; Watson, Judy J.; Roth, David M.; Patel, Hemal H.; Cannell, Mark B.; James, Andrew F.; Orchard, Clive H.
Abstract : New Findings: What is the central question of this study? What is the cellular basis of the protection conferred on the heart by overexpression of caveolin‐3 (Cav‐3 OE) against many of the features of heart failure normally observed in vivo ? What is the main finding and its importance? Cav‐3 overexpression has little effect in normal ventricular myocytes but reduces cellular hypertrophy and preserves t‐tubular I Ca, but not local t‐tubular Ca 2+ release, in heart failure induced by pressure overload in mice. Thus Cav‐3 overexpression provides specific but limited protection following induction of heart failure, although other factors disrupt Ca 2+ release. Abstract: Caveolin‐3 (Cav‐3) is an 18 kDa protein that has been implicated in t‐tubule formation and function in cardiac ventricular myocytes. During cardiac hypertrophy and failure, Cav‐3 expression decreases, t‐tubule structure is disrupted and excitation–contraction coupling (ECC) is impaired. Previous work has suggested that Cav‐3 overexpression (OE) is cardio‐protective, but the effect of Cav‐3 OE on these cellular changes is unknown. We therefore investigated whether Cav‐3 OE in mice is protective against the cellular effects of pressure overload induced by 8 weeks' transverse aortic constriction (TAC). Cav‐3 OE mice developed cardiac dilatation, decreased stroke volume and ejection fraction, and hypertrophy and pulmonary congestion in response to TAC. These changes were accompanied by cellular hypertrophy, a decrease in t‐tubule regularity and density, and impaired local Ca 2+ release at the t‐tubules. However, the extent of cardiac and cellular hypertrophy was reduced in Cav‐3 OE compared to WT mice, and t‐tubular Ca 2+ current ( I Ca ) density was maintained. These data suggest that Cav‐3 OE helps prevent hypertrophy and loss of t‐tubular I Ca following TAC, but that other factors disrupt local Ca 2+ release. Abstract :